Praktik Komunikasi Massa Komisi Pemilihan Umum Kabupaten Kediri dalam Sosialisasi Pemilu 2024 - Ellyda Retpitasari; M. Ilham Aditya Pratama; Imas Condro Kinasih; Irva Rahma Devi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The Democratic Party in Indonesia, often the spread of hoaxes occurs especially in the mass media, this affects people's perceptions of elections and candidates who are contesting the election. Media is an important element in political communication and socialization, which can influence a person's political attitude. The media can influence the attitudes of novice voters and first-time voters. The purpose of this research is to examine the mass communication of the General Election Commission in the implementation of a clean democracy, especially for novice voters, and can be more responsible for actively participating in the implementation of future elections. This research uses qualitative research through observation, interviews and documentation at the Kediri Regency General Election Commission. The results of this study refer to mass communication which is the most important thing in disseminating election information, the efficiency of its dissemination must also use the right media. Communicator experts use media quickly and periodically that expand messages to inform, influence, or spur change. All of that becomes effective election socialization, but it must be under intensive supervision so that there is no misunderstanding in the delivery of information.